2013
DOI: 10.1515/ncrs.2013.0219
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of μ-oxo-di-μ-sulfato-κ2O:O′-bis[(2,2′-bipyridine-κ2N,N′)-bis(dimethylsulfoxide-κO)-diiron(III)]monohydrate, C24H30Fe2N4O12S4

Abstract: Source of materialFeSO 4 ·7H 2 O(0.173 g, 0.62 mmol) was dissolved in methanol, to which was added solid 2,2'-bipyridine (0.049 g, 0.31 mmol) followed by triethylamine base (0.11 mL,0.78 mmol). The resulting blood red solution was stirred at room temperature for 5h.The solution was filtered and the solvent was evaporated under vacuo to obtainar ed solid. Crystallizationf romamethanol-dimethyl sulfoxide mixture (3:1) afforded green coloured crystals of the title compound after 15 days. Yield: 0.36 g, 72 %(based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Dynamics of MOCP in a solvent medium has attracted considerable interest in recent years for applications such as physical and chemical adsorption, ion exchange, sensor technology, drug delivery, and many more. Knowing that 1 has weakly hydrogen-bonded hydroxyl groups (from the monoprotonated dicarboxylic acid) within the chains, we then soaked 1 in several aqueous or ethanol or water/ethanol solutions of different divalent cation or anion precursors at room temperature, to investigate its dynamics in solvent medium. Under in situ observation using an optical microscope, overall, we found that soaking 1 in aqueous solutions of divalent cation or anion precursors exhibited the best properties in terms of visual changes, yielding single crystal products through the dissolution–recrystallization process with a measured pH in the range of 2–3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamics of MOCP in a solvent medium has attracted considerable interest in recent years for applications such as physical and chemical adsorption, ion exchange, sensor technology, drug delivery, and many more. Knowing that 1 has weakly hydrogen-bonded hydroxyl groups (from the monoprotonated dicarboxylic acid) within the chains, we then soaked 1 in several aqueous or ethanol or water/ethanol solutions of different divalent cation or anion precursors at room temperature, to investigate its dynamics in solvent medium. Under in situ observation using an optical microscope, overall, we found that soaking 1 in aqueous solutions of divalent cation or anion precursors exhibited the best properties in terms of visual changes, yielding single crystal products through the dissolution–recrystallization process with a measured pH in the range of 2–3.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there has been considerable interest in the dynamics of MOCP in solvent medium, often accompanied by structural transformations due to the dissolution–recrystallization process for applications such as physical and chemical adsorption, ion exchange, sensor technology, drug delivery, and many more. The structural transformation capability shall enhance with the use of a Pb­(II) cation due to its flexibility in adopting various donor atoms and coordination numbers as well as geometry (hemidirected or holodirected) . In fact, Vittal and co-workers as well as Morsali et.…”
Section: Introductionmentioning
confidence: 99%
“…Hydro- and solvothermal synthetic methods are convenient techniques for preparing metal–organic frameworks (MOFs) using aromatic dicarboxylic acid based ligands and transition elements, in particular, post-transition elements, with reported applications such as gas storage, magnetic, ,,, and luminescent applications. ,, The dissolution–crystallization method, a rather less popular technique and yet requires less synthetic equipment, could potentially produce a new, kinetically stable MOF that may merit its own structural library and applications. By a similar token of a facile dissolution–(re)-crystallization technique, postsynthetic modification of MOFs exploits the relatively weak coordination bond of certain metal centers to synthesize new compounds with tunable properties that are not possible through conventional synthetic pathways. , …”
Section: Introductionmentioning
confidence: 99%